2015
DOI: 10.1177/1352458515590648
|View full text |Cite
|
Sign up to set email alerts
|

Baseline clinical status as a predictor of methylprednisolone response in multiple sclerosis relapses

Abstract: Background: To date, there are no available factors to predict the outcome after multiple sclerosis relapse. Aim: To investigate factors that may be useful for predicting response to methylprednisolone treatment, following a relapse of multiple sclerosis (MS). Methods: The study included 48 MS patients enrolled in a double-blind multicenter trial to receive intravenous versus oral high-dose methylprednisolone treatment. Associations were sought between the disability status prior to relapse and the relapse sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Furthermore, the number of relapses within 2 years prior to fingolimod initiation was also an independent predictor for being relapse-free. These results are consistent with the previous findings, which demonstrated that a better clinical outcome was most influenced by immunomodulatory treatment and lower EDSS score change during the relapse [13, 14]. Of note, Hoepner et al identified an EDSS score >3 as a predictive factor for relapse; however, these observations were based on a different patient population comprising patients switching from natalizumab to fingolimod [15].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the number of relapses within 2 years prior to fingolimod initiation was also an independent predictor for being relapse-free. These results are consistent with the previous findings, which demonstrated that a better clinical outcome was most influenced by immunomodulatory treatment and lower EDSS score change during the relapse [13, 14]. Of note, Hoepner et al identified an EDSS score >3 as a predictive factor for relapse; however, these observations were based on a different patient population comprising patients switching from natalizumab to fingolimod [15].…”
Section: Discussionsupporting
confidence: 91%